IMPLEMENTASI STRATEGI PEMBELAJARAN VCT PADA PELAJARAN PAI DALAM MENYIKAPI KONFLIK SOSIAL DI SMK HARAPAN 1 RANCAEKEK BANDUNG - U. Abdullah Mukmin; Wati Karmila (Tadrib: Jurnal Pendidikan Agama Islam, 2021)
The purpose of this study was to work out the implementation of VCT (Value Clarification Technique) learning methods in Muslim Education lessons in responding to social conflicts at SMK Harapan one Rancaekek Bandung. This analysis uses a qualitative approach, with a descriptive analytic methodology. the info assortment uses interview, observation, and documentation techniques. Whereas knowledge analysis techniques through knowledge reduction, knowledge show, and drawing conclusions. The results of this study indicate that 1) RPP created by Curriculum Experts has not been fully maximized in the achievement of learning outcomes. 2) This VCT learning strategy is employed fitly, however there square measure many points that square measure uncomprehensible in its implementation. 3) The direct implication is that student’s square measure ready to show positive and negative attitudes through psychological feature, emotional and mental object responses. Whereas the indirect perspective of caring, tolerance, democracy, mutual cooperation, responsibility, and courtesy.